Pengaruh Pencampuran Tepung Ampas Kelapa dan Tepung Terigu terhadap Sifat Fisik, Organoleptik dan Daya Kembang Pancake - Seilatuw, Elstin; Oessoe, Yoakhim Y. E.; Lamaega, Jolanda Ch. E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The purpose of this study was to analyze the swelling power, crude fiber content, and determine the best organoleptic characteristics of pancakes by mixing coconut dregs flour and wheat flour. The research method used was a completely randomized design (CRD) with 4 treatments with a ratio of coconut dregs flour and wheat flour, namely P1 (control), P2 (10%:90%), P3 (20%:80%), and P4 (30%:70%). Each treatment consisted of 3 repetitions. The research data were processed using ANOVA and continued with the LSD test at the 5% test level, if there was an effect between treatments. The results of the research on swelling power ranged from 35.42-44.2% with the highest swelling value obtained by pancakes with a mixture of 0% coconut dregs flour. Based on the organoleptic test, mixing 20% coconut dregs flour obtained the highest level of preference, with a rating of 4.48-5 (netral-rather like). Crude fiber content ranges from 2.06-3.81%. Pancakes mixed with 30% coconut flour had the highest crude fiber content.